INTEGRATIVE APPROACH TO CORRECTING NEUROCOGNITIVE DISORDERS IN CHILDREN WITH ASD USING PSYCHOMOTOR THERAPY - T.B. Irmukhamedov (KONFERENSIYALAR, 2025)
Introduction. It is known that the leading criteria for assessing a child’s health are the state of mental and motor functioning. A delay in the development of motor activity, in turn, can cause a delay in the mental development of the child, since these two important areas of activity represent the most important basis in understanding the surrounding picture of the world.